Associations between ambient air pollution and IVF outcomes in a heavily polluted city in China. Issue 1 (January 2022) - Liu, Jing; Zhao, Mingpeng; Zhang, Haoyang; Zhao, Junliang; Kong, Hongjiao; Zhou, Mengge; Guan, Yichun; Li, Tin Chiu; Wang, Xingling; Chan, David Yiu Leung
Abstract: Research question: Is air pollution related to IVF outcomes in a heavily polluted city in China? Design: A retrospective cohort study of 8628 fresh, autologous IVF cycles was conducted for the first time at the Reproductive Medicine Center of The Third Affiliated Hospital of Zhengzhou University between May 2014 and December 2018 (oocyte retrieval date). The exposure was divided into four periods (gonadotrophin injection to oocyte retrieval [P1], oocyte retrieval to embryo transfer [P2], 1 day after embryo transfer to embryo transfer +14 days [P3] and gonadotrophin injection to embryo transfer +14 days [P4]) and four levels (Q1–Q4 according to their 25th, 50th and 75th percentiles). Results: An interquartile range increase (Q2 versus Q1) in particulate matter ≤10 µm (PM10) during P3 and P4 and sulphur dioxide (SO2 ) during P3 significantly decreased the clinical pregnancy rate (adjusted odds ratio [aOR] 0.81, 95% confidence interval [CI] 0.71–0.92 for PM10 of P3; aOR 0.87, 95% CI 0.76–1.00 for PM10 of P4; aOR 0.82, 95% CI 0.73–0.93 for SO2 of P3). In addition, PM10 was associated with an increased biochemical pregnancy rate (Q3 versus Q1: aOR 1.55, 95% CI 1.09–2.19 for PM10 of P1) and decreased live birth rate (Q2 versus Q1: aOR 0.88, 95% CI 0.77–0.99 for PM10 of P3). The multivariate regression results were consistent with that of multiple treatments propensity score method (PSM) for SO2 pollutants in P3 and PM10 pollutants in P4. Conclusion: From the early follicular stage to the pregnancy test period, high concentrations of PM10 and SO2 may have a negative impact on IVF treatment outcomes in the study area.